The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1104/pp.71.2.362
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Abscisic Acid in Potato Cold Acclimation

Abstract: The possible significance of specific biochemical changes in relation to cold acclimation has been discussed extensively (13), but causal relationship between metabolic changes and cold acclimation is difficult to establish. Generally, the development of frost hardiness has been reported to be accompanied with changes in hormones (12,19,24), and in quality and quantity of proteins (14,16). Under a low temperature regime, an increase in leaf soluble protein content was observed only in those potato species whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
145
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(155 citation statements)
references
References 21 publications
(14 reference statements)
8
145
1
Order By: Relevance
“…Low soil temperatures are known to inhibit L p and induce stomatal closure in aspen (Wan et al, 1999). It is possible that, like low root temperature (Chen et al, 1983;Lee et al, 1993) and drought (Zhang et al, 1987;Lång et al, 1994), HgCl 2 treatment triggered ABA synthesis, which directly caused stomatal closure. This could explain the slow recovery of stomatal opening following ME treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Low soil temperatures are known to inhibit L p and induce stomatal closure in aspen (Wan et al, 1999). It is possible that, like low root temperature (Chen et al, 1983;Lee et al, 1993) and drought (Zhang et al, 1987;Lång et al, 1994), HgCl 2 treatment triggered ABA synthesis, which directly caused stomatal closure. This could explain the slow recovery of stomatal opening following ME treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Through the cold acclimation process, reprogramming of gene expression and various modifications in the metabolism take place (Chinnusamy et al 2010). Acclimation also causes an increase in the production of antioxidants, abscisic acid (ABA) and compatible osmolytes such as soluble sugars and proline (Lynch & Steponkus 1987;Koster & Lynch 1992;Chen et al 1993;Kishitani et al 1994;Uemura & Steponkus 1994;Murelli et al 1995;Nomura et al 1995;Dörffling et al 1997;Tao et al 1998). Denesik (2007) reported that cold treatment affects membrane fluidity resulting in an increase in the membrane rigidity.…”
Section: Cold Acclimation and Frost Stress Tolerancementioning
confidence: 99%
“…In general, there were parallel changes between the ABA contents and freezing tolerance development. Several types of evidence have suggested that ABA-controlled processes are central to cold acclimation and development of freezing tolerance in herbaceous plants, i.e., the low temperature stimulus can be substituted by exogenous ABA, resulting in an increase in freezing tolerance at normal growth temperatures (Chen et al 1983, Lång et al 1989, Mäntylä et al 1995, Tamminen et al 2001; endogenous ABA contents can be enhanced by LT both in chilling-sensitive (Daie andCampbell 1981, Pan 1990), chilling-tolerant annual (Chen et al 1983, Guy andHaskell 1988), and overwintering (Lalk and Dörffling 1985) species. In our study, there were corresponding differences between the ecotypes in ABA alterations during cold acclimation: compared with the low altitudinal ecotype, ABA contents of the high altitudinal ecotype was more responsive to SD and LT.…”
Section: Discussionmentioning
confidence: 99%